Mills in Charcas, Córdoba and Buenos Aires (1550-1600) [Molinos y Tahonas en Charcas, Córdoba y Buenos Aires (1550-1600)] - Lacoste, P; Soto-González, N (Universidad Catolica del Norte, 2022)
This paper examines the expansion of flour mills in the Audiencia de Charcas during the second half of the 16th century. The largest hydro-milling center in the Americas emerged in Alto Peru (present-day Bolivia), around Chuquisaca and Cochabamba, where about a hundred mills operated. The technology spread southward, particularly to Córdoba. The mills had a social impact, consolidating a stately society with strongly defined hierarchies. Politically, their significance was in the status that the technology brought to cities, which then became the seat of audencias and universities. © Este es un artículo de acceso abierto bajo licencia Creative Commons BY 4.0